PENGARUH KRISIS MONETER, NILAI TUKAR, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - D.N Nirmaya; F.F Farabi; I. A. Lumbantobing (Jurnal Pendidikan Ekonomi Indonesia, 2020)
Due to the low economic growth in Indonesia, which is indicated by the low fundamentals of the Indonesian economy as a result of the global crisis that has hit the world today. This study aims to determine the effect of the monetary crisis, exchange rate, and inflation on economic growth in Indonesia by reviewing and summarizing its track record through existing data including (1) Rupiah Exchange Rate 1990-2010; (2) Indonesia's inflation from 1990-2010; and (3) Indonesia's GDP in the years 2990-2010 which the authors have obtained data from BPS and other sources. The data analysis method in this research uses a quantitative model on OLS (Ordinary Least Squared). The results showed that the monetary crisis as a Dummy variable, exchange rate, and inflation had a significant and significant effect on economic growth in Indonesia.